A New Etiologic Factor for Adnexal Torsion: Congenital Omental Fenestrum - Ulaş Fidan; Fahri Burçin Fıratlıgil; Mustafa Ulubay; Uğur Keskin; Ali Ergün (Medical Network, 2016)
Torsion seen in ovary, fallopian tube or in both organs is one of the gynecologic emergency pathologies in patients suffering from acute lower abdominal pain, and it constitutes approximately 2.7% of gynecologic emergencies. Delays in diagnosis and treatment can cause ischemic damage, in that way can cause the risk of ovary, fallopian tube or both organs loss. Thus, it can result in fertility problems in people who are desiring future fertility. Although the etiology is not totally known, it has been thought that torsion risk has been increasing in benign cystic teratomas and ovarian tumors. It can be also seen in congenital situations such as vitellointestinal duct anomaly and people who have undergone pelvic surgery. In this article, a case for adnexal torsion developed in congenital omental fenestrum which is considered as a new factor for torsion etiology, was explained.